The Relationship Between Muslim Directors on Board of Directors and Audit Committee Characteristics on Performance Evidence from Jordan - Saddam Ali Shatnawi; Mustafa Mohd Hanefah; Monther Eldaia; Bilal Khalaf Sakarneh (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 26-36